Exploring leadership behaviors of the coaches of champion teams - Yenen, Eda; Atamturk, Hakan; Atamturk, Nurdan (Frontiers in Psychology, 2023)
Participation in sports at school is highly valued since it is believed that it develops students’ social skills and adds to personal development. Owing to the fact that the behaviors of the coaches have an important effect on the development of the student athletes, this quantitative study was designed with the aim to evaluate the perceptions of young student athletes of the champion school teams of their coaches’ leadership behaviors. The study also sought to determine the variables affecting these perceptions. A total of 236 young student athletes who were the members of the champion teams of basketball, handball, volleyball, futsal, badminton, wrestling and swimming in the period of 2021–2022 evaluated their coaches’ leadership qualities. One of the major results was that the young student athletes had positive perceptions of their coaches. Adopting Chelladurai’s model, training and instruction was found to be particularly important in achieving high performance. More specifically, the Mann Whitney U test results revealed that the athletes’ perceptions differed by gender and by being involved in team or individual sports; however, Kruskal-Wallis test revealed perceptions did not differ by age. The significance of this study lies in its practical implications for sport coaches, coaching practice, physical education teachers and practitioners in sport psychology.